Preventive Medicine in Islam | الطب الوقائي في الإسلام - Aminah Iraqi (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2016)
This article talks about Islam as religion and it’s contribution for the medicine sciences.Islam suggests to maintain health and health treatment, because it’s included Islamicreligious spirit. Moslem will pray for the God well with a good condition of his heath.This article refuted the statement that Islam is a religion afterlife, and Islam don’t give agood attention to the health aspects of the world. This article will show some verses andprophet tradition on maintain helath and how to get health in this life.